Metodologia para avaliação da sustentabilidade de operações de transporte urbano de carga - Bandeira, Renata Albergaria de Mello (2018)
This research aims to propose a methodology for assessing the sustainability of urban freight transport (UFT) operations, according to the perspective of transport operators. This methodology fills some gaps identified in the existing literature, such as: the lack of studies regarding the criteria that should be assessed by operators in order to select the best suited UFT initiative to increase its sustainability level, as well as the absence of indicators or an index for such analysis. Therefore, a set of sustainability transportation indicators were identified and then adapted for evaluating the sustainability of UFT operations. Such indicators are the basis for the sustainability index for UFT proposed in this thesis. In order to estimate this index, we develop a fuzzy multi-criteria model, considering not only uncertainty but also different weights for various indicators. Moreover, this index limits the amount of information presented, allowing companies and transportation operators to develop comparative analyzes to evaluate alternative configurations for their collection, transfer and load distribution chains and then classify them in terms of sustainability. We apply the proposed methodology in a case study in order to assess the adoption of tricycles and electric light commercial vehicles as alternatives to the last mile of postal distribution, through a case of a public company in Rio de Janeiro, Brazil. This application confirmed the consistency, simplicity, flexibility and applicability of the proposed methodology.